How public policy can stimulate the capabilities of firms to innovate in a traditional industry through academic engagement: the case of the Swedish food industry. (15th July 2016) - McKelvey, Maureen; Ljungberg, Daniel
Abstract : This paper shows how public policy can stimulate innovation in low‐ and medium‐technology industries, by connecting firms and universities through collaborative scientific research. A conceptual framework proposes that collaborative research between universities and firms may result in tangible innovative outcomes, such as new or improved products or processes, and intangible outcomes that strengthen firms' internal capabilities and thereby indirectly increase their innovativeness. Findings are presented from a case study of a Swedish public policy stimulating the development of firm capabilities for innovation, through collaborative research projects connecting universities and firms in the food industry between 1998 and 2006. In line with the conceptual framework, the analysis distinguishes between (i) direct outcomes, such as new products; and (ii) indirect outcomes in the form of the development of firms' capabilities to innovate. Based on this analysis, the initial conceptual framework is expanded to indicate how policy can stimulate the development of firms' capabilities.